2016
DOI: 10.3174/ajnr.a4731
|View full text |Cite
|
Sign up to set email alerts
|

A New Ultrasound Marker for Bedside Monitoring of Preterm Brain Growth

Abstract: BACKGROUND AND PURPOSE:Preterm neonates are at risk for neurodevelopmental impairment, but reliable, bedside-available markers to monitor preterm brain growth during hospital stay are still lacking. The aim of this study was to assess the feasibility of corpus callosum-fastigium length as a new cranial sonography marker for monitoring of preterm brain growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 32 publications
3
26
0
Order By: Relevance
“…Similarly, Anderson et al 9 showed that postnatal growth of the CCL in verylow-birth-weight infants approximated fetal growth (1.4 -1.89 mm/week PMA) within the first 2 postnatal weeks but subsequently slowed to approximately half of that expected. 22,23 Moreover, the current study found that a BW z score of ϽϪ2 SDs was associated with slower CCL growth from birth to TEA, a finding consistent with that of Roelants et al 10 The TCD measured in the fetus, or the neonate in the first postnatal days, is a reliable marker of GA, even with fetal growth restriction, small-and large-for-gestational age fetuses, and multiple gestations (1.25-1.89 mm/week PMA). [24][25][26][27] Cross-sectional preterm MR imaging studies have reported cerebellar size, but our study is the first to report postnatal growth of the TCD in preterm infants using sequential cUS.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Similarly, Anderson et al 9 showed that postnatal growth of the CCL in verylow-birth-weight infants approximated fetal growth (1.4 -1.89 mm/week PMA) within the first 2 postnatal weeks but subsequently slowed to approximately half of that expected. 22,23 Moreover, the current study found that a BW z score of ϽϪ2 SDs was associated with slower CCL growth from birth to TEA, a finding consistent with that of Roelants et al 10 The TCD measured in the fetus, or the neonate in the first postnatal days, is a reliable marker of GA, even with fetal growth restriction, small-and large-for-gestational age fetuses, and multiple gestations (1.25-1.89 mm/week PMA). [24][25][26][27] Cross-sectional preterm MR imaging studies have reported cerebellar size, but our study is the first to report postnatal growth of the TCD in preterm infants using sequential cUS.…”
Section: Discussionsupporting
confidence: 91%
“…The cUS linear measures explored in this study had well-defined anatomic landmarks on standard imaging planes obtained during routine clinical care, and several showed excellent intra-and interobserver reproducibility, as also shown by others. 8,10,16,17 Although cUS affords an opportunity to make sequential measurements from birth, there are limited published data relating to postnatal brain growth in preterm infants. To our knowledge, this study is the first to describe the growth of the BPD in the early postnatal period following preterm birth using sequential cUS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(CCF) length is a reliable bedside-available US marker that can be used to monitor brain growth in preterm infants during neonatal intensive care unit stays. 13 CCF length is considered a composite marker of diencephalon and mesencephalon size and thereby adds information to the more widely used corpus callosum (CC) length. 13 We hypothesized that these 2 cranial ultrasound measures are feasible for use during prenatal US examinations.…”
mentioning
confidence: 99%
“…13 CCF length is considered a composite marker of diencephalon and mesencephalon size and thereby adds information to the more widely used corpus callosum (CC) length. 13 We hypothesized that these 2 cranial ultrasound measures are feasible for use during prenatal US examinations. Thereby, these markers would provide a continuum for monitoring brain growth, bridging the period before and after birth.…”
mentioning
confidence: 99%